Digital Branding of Lembaga Jaminan Halal in Indonesia - Aprieleony, Wima; Aisyah, Vinisa Nurul (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2022)
Purpose: The purpose of this research is to determine how BPJPH's digital branding on social media. Methodology: This study uses a qualitative method with a descriptive case study. The data collection in this study was done by interviewing the Sub Coordinator of Information Systems and Public Relations and the BPJPH's Public Relations Team, as well as making observations on BPJPH's social media. Researchers use the theory of Branding according to Kotler. Results: The results of the study found that branding was implemented through several elements, namely brand positioning, brand personality, brand identity, and brand awareness on BPJPH's social media. In its implementation, this element is carried out by the BPJPH's public relations team. Applications/Originality/Value: The object of this research is BPJPH, because BPJPH is an institution that has an important role in halal certification and is also a new institution that requires a study.